Meridional variations of C2H2 and C2H6 in Jupiter's atmosphere from Cassini CIRS infrared spectra - Nixon, C; Achterberg, R; Conrath, B; Irwin, P; Teanby, N; Fouchet, T; Parrish, P; Romani, P; Abbas, M; LeClair, A; Strobel, D; Simon-Miller, A; et al. (2007)
Hydrocarbons such as acetylene (C2H2) and ethane (C2H6) are important tracers in Jupiter's atmosphere, constraining our models of the chemical and dynamical processes. However, our knowledge of the vertical and meridional variations of their abundances has remained sparse. During the flyby of the Cassini spacecraft in December 2000, the Composite Infrared Spectrometer (CIRS) instrument was used to map the spatial variation of emissions from 10 to 1400 cm-1 (1000-7 μm). In this paper we analyze a zonally averaged set of CIRS spectra taken at the highest (0.48 cm-1) resolution, firstly to infer atmospheric temperatures in the stratosphere at 0.5-20 mbar via the ν4 band of CH4, and in the troposphere at 150-400 mbar, via the H2 absorption at 600-800 cm-1. Stratospheric temperatures at 5 mbar are generally warmer in the north than the south by 7-8 K, while tropospheric temperatures show no such asymmetry. Both latitudinal temperature profiles however do show a pattern of maxima and minima which are largely anti-correlated between the two levels. We then use the derived temperature profiles to infer the vertical abundances of C2H2 and C2H6 by modeling tropospheric absorption (∼200 mbar) and stratospheric emission (∼5 mbar) in the C2H2ν5 and C2H6ν9 bands, and also emission of the acetylene (ν4 + ν5) - ν4 hotband (∼0.1 mbar). Acetylene shows a distinct north-south asymmetry in the stratosphere, with 5 mbar abundances greatest close to 20° N and decreasing from there towards both poles by a factor of ∼4. At 200 mbar in contrast, acetylene is nearly flat at a level of ∼ 3 × 10-9. Additionally, the abundance gradient of C2H2 between 10 and 0.1 mbar is derived, based on interpolated temperatures at 0.1 mbar, and is found to be positive and uniform with latitude to within errors. Ethane at both 5 and 200 mbar shows increasing VMR towards polar regions of ∼1.75 towards 70° N and ∼2.0 towards 70° S. An explanation for the meridional trends is proposed in terms of a combination of photochemistry and dynamics. Poleward, the decreasing UV flux is predicted to decrease the abundances of C2H2 and C2H6 by factors of 2.7 and 3.5, respectively, at latitude 70°. However, the lifetime of C2H6 in the stratosphere (3 × 1010   s at 5 mbar) is much longer than the dynamical timescale for meridional mixing inferred from Comet SL-9 debris (5 - 50 × 108   s), and therefore the rising abundance towards high latitudes likely indicates that meridional mixing dominates over photochemical effects. For C2H2, the opposite occurs, with the relatively short photochemical lifetime (3 × 107   s), compared to meridional mixing times, ensuring that the expected photochemical trends are visible. © 2006 Elsevier Inc. All rights reserved.